Regulation of proteasome assembly and activity in health and disease. Issue 11 (November 2018) - Rousseau, Adrien; Bertolotti, Anne
Abstract The proteasome degrades most cellular proteins in a controlled and tightly regulated manner and thereby controls many processes, including cell cycle, transcription, signalling, trafficking and protein quality control. Proteasomal degradation is vital in all cells and organisms, and dysfunction or failure of proteasomal degradation is associated with diverse human diseases, including cancer and neurodegeneration. Target selection is an important and well-established way to control protein degradation. In addition, mounting evidence indicates that cells adjust proteasome-mediated degradation to their needs by regulating proteasome abundance through the coordinated expression of proteasome subunits and assembly chaperones. Central to the regulation of proteasome assembly is TOR complex 1 (TORC1), which is the master regulator of cell growth and stress. This Review discusses how proteasome assembly and the regulation of proteasomal degradation are integrated with cellular physiology, including the interplay between the proteasome and autophagy pathways. Understanding these mechanisms has potential implications for disease therapy, as the misregulation of proteasome function contributes to human diseases such as cancer and neurodegeneration. Protein degradation by the proteasome is crucial for the control of many cellular processes, and defects in proteasomal degradation may lead to cancer and neurodegeneration. TOR complex 1 has a key role in regulating proteasome abundance and assembly and in integrating proteasomal activity with autophagy pathways and, more generally, cell physiology.